1999
DOI: 10.1259/bjr.72.861.10645189
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anatomical analysis of arterial contact with trigeminal nerve: detection with three-dimensional spoiled grass imaging.

Abstract: The purpose of this study was to review the normal in vivo neurovascular relationship between the trigeminal nerve and surrounding arteries without the use of volunteers. 290 nerves in 145 cases were reviewed during a 1-year period. Axial source images and multiplanar reconstructed (MPR) images were used to determine the neurovascular contact and direction of contact. Multiplanar volume reformation (MPVR) was used to identify the contact vessels and to demonstrate the relationship between the nerve and arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
2
12
1
Order By: Relevance
“…As one of the important arteries in the posterior fossa, SCA has close relation with CN-III, CN-IV, CN-V. Of the offending vessels to trigeminal nerve root, SCA accounts for the largest proportion, which was 78% reported by Ueda F, (22) and 60.6% in our series. SCA originates from the basilar artery going posteriorly to supply the cerebellum and brain stem.…”
Section: Superior Cerebellar Artery (Sca)supporting
confidence: 51%
“…As one of the important arteries in the posterior fossa, SCA has close relation with CN-III, CN-IV, CN-V. Of the offending vessels to trigeminal nerve root, SCA accounts for the largest proportion, which was 78% reported by Ueda F, (22) and 60.6% in our series. SCA originates from the basilar artery going posteriorly to supply the cerebellum and brain stem.…”
Section: Superior Cerebellar Artery (Sca)supporting
confidence: 51%
“…Other studies have reported similar or even higher prevalences (18%, 28%, 71%) of vascular conflicts on the healthy side. [15][16][17] Autopsy series also show vascular compression of the trigeminal nerve in individuals who never had TN. 18,19 The use of MVD is widely accepted, but whether vascular compression is the exact cause of TN remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ueda et al (1999) conducted an in-vivo MRI study in 145 volunteers (290 REZ), which included 4 REZ with trigeminal neuralgia ( Table 5). 8 They used multiplanar volume reformation (MPVR) to delineate the REZ. Yousry et al (2005) also conducted an MRI study of 33 volunteers and 7 cadavers, with a total of 80 REZ.…”
Section: Discussionmentioning
confidence: 99%